The Integration of Islamic Da'wah and Education in Fostering Youth Morality within the Digital Era - Istihabul Imamah; Ragwan Albaar (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
ENGLISH: The Integration of Islamic Da'wah and Education in Fostering Youth Morality within the Digital EraObjective: This study aims to formulate an integration model of Islamic dawah and education as a moral reinforcement strategy for the younger generation in facing digital era challenges. Method: The study employs a qualitative approach with the Directed Qualitative Content Analysis (DQCA) method through the analysis of literature and scientific documents using a directed coding process. Findings: The results indicate that the implementation of digital dawah along with formal, nonformal, and informal education still operates in a fragmented manner, thereby failing to form an integrated moral development system. Furthermore, the dynamics of social media algorithms, unfiltered information flows, and low digital literacy heighten the vulnerability of the younger generation to moral degradation. Conclusion: The integration model of Islamic dawah and education provides a theoretical foundation as well as practical guidelines for educators, dawah practitioners, parents, and policymakers in designing moral development strategies for the younger generation that are adaptive, collaborative, sustainable, and relevant to digital technological advancements. Contribution: This study offers the Dawah Didik Model as a new integrative framework that comprehensively aligns a value-based curriculum, contextual dawah, and digital parenting.INDONESIAN: Integrasi Dakwah Islam dan Pendidikan dalam Pembentukan Moral Generasi Muda di Era DigitalTujuan: Penelitian ini bertujuan merumuskan model integrasi dakwah Islam dan pendidikan sebagai strategi penguatan moral generasi muda dalam menghadapi tantangan era digital. Metode: Penelitian menggunakan pendekatan kualitatif dengan metode Directed Qualitative Content Analysis (DQCA) melalui analisis literatur dan dokumen ilmiah menggunakan pengodean terarah. Hasil: Temuan menunjukkan bahwa implementasi dakwah digital serta pendidikan formal, nonformal, dan informal masih berlangsung secara parsial sehingga belum membentuk sistem pembinaan moral yang terpadu. Selain itu, dinamika algoritma media sosial, arus informasi tanpa filter, dan rendahnya literasi digital turut meningkatkan kerentanan generasi muda terhadap degradasi moral. Kesimpulan: Model integrasi dakwah islam dan pendidikan memberikan landasan teoretis sekaligus panduan praktis bagi pendidik, dai, orang tua, dan pemangku kebijakan dalam merancang strategi pembinaan moral generasi muda yang adaptif, kolaboratif, berkelanjutan, serta relevan dengan perkembangan teknologi digital. Kontribusi: Penelitian ini menawarkan Model Dakwah-Didik sebagai kerangka integratif baru yang menyelaraskan kurikulum berbasis nilai, dakwah kontekstual, dan pengasuhan digital secara komprehensif.